An optimal electrolyte addition strategy for improving performance of a vanadium redox flow battery. (15th January 2020) - Lu, Mengyue; Yang, Weiwei; Deng, Yiming; Xu, Qian
Summary: In this paper, the influences of multistep electrolyte addition strategy on discharge capacity decay of an all vanadium redox flow battery during long cycles were investigated by utilizing a 2‐D, transient mathematical model involving diffusion, convection, and migration mechanisms across the membrane as well as the contact resistance in the battery. Results show that with various multistep electrolyte addition strategies, the discharge capacity decay of the battery can be diminished. An optimal multistep electrolyte addition strategy is presented, which is corresponding to adding 1.04 mol L −1 V 3+ electrolyte to a negative tank while adding 1.04 mol L −1 VO2 + electrolyte to a positive tank. Results show that capacity decay of the battery can be debased by 10.8%, which is due to increased vanadium ions in the negative side and the decreased state‐of‐charge (SOC) imbalance between two half‐cells. This study will propose a practical method for mitigating the discharge capacity decay of the battery during operation. Abstract : A vanadium redox flow battery (VRFB) model involving diffusion, convection, and migration mechanisms as well as the contact resistance was presented. Optimal multistep electrolyte addition strategy was proposed and examined. Discharge capacity decay of the battery was obviously improved with optimal multistep electrolyte addition strategy.